2019
DOI: 10.1177/1753193419873230
|View full text |Cite
|
Sign up to set email alerts
|

Elektra prosthesis versus resection-suspension arthroplasty for thumb carpometacarpal osteoarthritis: a long-term cohort study

Abstract: The present study compares 34 patients with thumb carpometacarpal osteoarthritis (37 thumbs) treated with the Elektra® prosthesis, with 18 patients (18 thumbs) treated with resection-suspension arthroplasty, with an overall mean follow-up period of 13.3 years. Evaluation with disability of arm and shoulder scores, pain via visual analogue scale and range of motion (radial and palmar abduction, and opposition) indicated no significant difference. However, the cohort with a surviving prosthesis showed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 25 publications
1
35
1
Order By: Relevance
“…Moreover, reliability testing was performed in a relatively small group of 29 young subjects with physiological anatomy of the hand. Moreover, due to our healthy study cohort, whose subjects do not suffer from any thumb CMC condition, and thus no pathological ROM impairment, we were not able to assess opposition ROM measurement methods, because all subjects would have reached 10 points in the Kapandji Score [25] or 0 centimetre distance between the thumb tip and the fifth metacarpophalangeal joint [6]. Future studies are required to validate the usefulness, applicability, and reliability of all the investigated methods for patients suffering from any condition concerning the thumb CMC joint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, reliability testing was performed in a relatively small group of 29 young subjects with physiological anatomy of the hand. Moreover, due to our healthy study cohort, whose subjects do not suffer from any thumb CMC condition, and thus no pathological ROM impairment, we were not able to assess opposition ROM measurement methods, because all subjects would have reached 10 points in the Kapandji Score [25] or 0 centimetre distance between the thumb tip and the fifth metacarpophalangeal joint [6]. Future studies are required to validate the usefulness, applicability, and reliability of all the investigated methods for patients suffering from any condition concerning the thumb CMC joint.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, radial and palmar abduction measurements, [4][5][6] whose terms imply their respective movement planes (i.e. parallel and perpendicular to the palm), currently represent the most frequently applied methods for examining restrictions of ROM caused by thumb CMC conditions, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, embarking on a randomized controlled study comparing trapeziectomy with any TMC total arthroplasty, particularly a new one, carries the risk of becoming irrelevant. This is as the joint replacement, however well it performs in the short-term, may be found to have an unacceptably high revision rate (Craik et al., 2017; Froschauer et al., 2020; Kollig et al., 2017) such that it is withdrawn from the market. Some implants appears to survive better than others (Aebischer et al., 2016), but only when a total joint replacement is shown to have acceptably low long-term failure rates (ideally at 10 years) when inserted by the majority of hand surgeons, will the time be right for such a comparative trial.…”
Section: What Is the Best Surgical Technique For Tmc Osteoarthritis?mentioning
confidence: 99%
“…In addition to corticosteroids, injection-based treatment using hyaluronic acid, saline placebo, and dextrose were compared in a recent meta-analysis which concluded that there was no clear evidence whether any injected substance was superior to others or that one of them was better than another conservative treatment option [ 4 ]. As a further consequence, if non-operative treatment fails, a wide range of different surgical methods are available, for example, denervation, partial or total trapeziectomy, resections-suspension arthroplasty with use of various adjacent tendons, arthrodesis, and total arthroplasty with a huge number of various prosthesis types [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%